Molecular studies of lung neuroendocrine neoplasms uncover new concepts and entities - Fernandez-Cuesta, Lynnette; Foll, Matthieu (Translational Lung Cancer Research, 2019)
Lung neuroendocrine neoplasms (NENs) account for up to 25% of all lung cancers and can be subdivided into poorly differentiated, high-grade neuroendocrine carcinomas (NECs) including small cell lung carcinoma (SCLC, 20%) and large-cell neuroendocrine carcinomas (LCNEC, 3%), and well-differentiated neuroendocrine tumours (NETs, 2%) including the low- and intermediate-grade typical and atypical carcinoids, respectively (1).